The book of charlatans = Kitāb al-Mukhtār fī kashf al-asrār - Jawbarī, ʻAbd al-Raḥmān ibn ʻUmar, active 1216-1222 (Library of Arabic literature., 2020)
"A comprehensive guide to trickery and scams as practiced in the thirteenth century in the cities of the Middle East, especially in Syria and Egypt"--